2021
DOI: 10.1002/jmv.27215
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone treatment may mitigate adverse effects of vitamin D deficiency in hospitalized Covid‐19 patients

Abstract: Aims We have previously demonstrated that vitamin D deficiency might be associated with worse outcomes in hospitalized Covid‐19 patients. The aim of our study was to explore this relationship with dexamethasone therapy. Methods We prospectively studied two cohorts of hospitalized Covid‐19 patients between March and April and between September and December 2020 ( n = 192). Patients were tested for serum 25‐hydroxyvitamin D (25‐OH‐D) levels duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The complex interaction of Vit D and corticosteroids (CRTs) in vivo may partially explain the conflicting outcomes observed in the COVID-19 literature, and previous studies on Vit D have been insufficiently powered to detect this interaction [ 55 , 56 , 57 , 58 , 59 ]. Glucocorticoids can inactivate Vit D by upregulating Vit D receptor (VDR)-mediated 24-hydroxylase transcription through the cooperative relationship of CCAAT-enhancer-binding proteins (C/EBPβ) and glucocorticoid receptors (GRs) [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…The complex interaction of Vit D and corticosteroids (CRTs) in vivo may partially explain the conflicting outcomes observed in the COVID-19 literature, and previous studies on Vit D have been insufficiently powered to detect this interaction [ 55 , 56 , 57 , 58 , 59 ]. Glucocorticoids can inactivate Vit D by upregulating Vit D receptor (VDR)-mediated 24-hydroxylase transcription through the cooperative relationship of CCAAT-enhancer-binding proteins (C/EBPβ) and glucocorticoid receptors (GRs) [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the use of dexamethasone in COVID-19 patients can lead to a reduction in D-dimer levels [ 76 , 77 ]. While some studies have suggested that dexamethasone can reduce D-dimer levels in COVID-19 patients [ 78 , 79 ], other studies have found no significant effect [ 80 , 81 , 82 ]. While there have been some studies that have shown a reduction in D-dimer levels with the use of IL-6 antagonists in COVID-19 patients, other studies have found no significant effect on D-dimer levels.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D status may interact with other treatments for COVID-19. Investigators in the UK compared outcomes associated with vitamin D status before (March–April 2020) and after (September–December 2020) the use of dexamethasone in hospitalized patients [ 30 ]. Vitamin D deficiency was associated with elevated CRP and need for ventilation in hospitalized COVID-19 patients prior to use of dexamethasone but not during the interval of dexamethasone use.…”
Section: Observational Studiesmentioning
confidence: 99%